Dancers of the Ivory Coast - Ferguson, Isabel (International Library of African Music, 1962)
A project is afoot in the Ivory Coast to form a national theatre, one that would include dance, drama and the making of films. Though an ambitious undertaking for any country, it is especially so for a new nation when economic, social, and educational problems loom large. The aim of this enterprise is to help create a national image; to put the Ivory Coast on the map, show its multifaceted culture, and give encouragement to its musicians, writers, dancers, and other artistic people. As more and more contacts are made on the cultural level, nations of diverse background and training find they share a more equal footing and have better grounds for mutual understanding and appreciation.
Keywords: Ethnomusicology; Dance; Côte d'Ivoire; African Music